Corporate Social Responsibility: Education on F&B Business Development at Kopi Kabi - Jasmine Nur’Aini Azizah; Farida Nurfalah (Siber Nusantara Research, 2026)
This research is motivated by the rapid growth of the coffee industry and F&B businesses, which encourages companies to focus not only on profit but also on social engagement. The study aims to analyze the implementation of education-based CSR at Kopi Kabi, its impact on business development, and the factors influencing its effectiveness. The study used a descriptive qualitative approach through interviews, observations, and documentation with purposively selected informants. The results show that the educational CSR program was implemented flexibly according to community needs and received a positive response from stakeholders. This program improved the skills, knowledge, and confidence of participants and encouraged entrepreneurial activity in the F&B sector. The program's effectiveness was influenced by its alignment with community needs, stakeholder support, accountability, and the company's adaptability. These findings confirm that educational CSR plays a strategic role in building social legitimacy and business sustainability.